Identificación y caracterización de mecanismos de resistencia a herbicidas inhibidores de la enzima acetohidroxiácido sintasa en girasol - Gil, Mercedes (2017)
Imidazolinone (IMI) resistance genes have been introgressed from a sunflower wiid population collected in Kansas to elite inbred lines. A digenic model has been proposed as the genetic basis of the inheritance of IMI resistance. This model assumes that both parents must express two resistance genes to achieve complete resistance in the hybrids: the major semidominant locus lmr1, an allelic variant of the ahas1 locus that codes for the acetohydroxyacid synthase catalytic subunit and the modifier locus lmr2, whose effect remains unknown and it could be related to non-target-site resistance such as xenobiotic metabolism. The objective of this study was to identify and characterize IMI resistance mechanisms in sunflower. Specific objectives were: 1- Evalúate the growth response to imazetapyr in combination with P450s inhibitor piperonyl butoxide (PBO) ¡n sunflower plantlets. 2- Evaluate the growth response to imazetapyr ¡n combination with P450s inhibitor 1-aminobenzotriazole (ABT) in sunflower plantlets. 3- Characterize sunflower gene expression in response to imazetapyr using cDNA-AFLP. 3.1- Determine the optimal herbicide concentration known as discríminating dose. 3.2- Determine optimal herbicide treatment length. 3.3- Determine acetohydroxyacid synthase in vitro activity to assess enzyme inhibition levéis. 4- Characterize resistant sunflower gene expression in response to imazetapyr using TruSeq Stranded RNA-Seq. Two sunflower inbred lines were used ¡n this study: HA 425 and HA 89, classified as resistant (lmr1lmr1lmr2lmr2) and susceptible (¡mr1imr1imr2imr2), respectively. An important number of xenobiotic metabolism related genes were found in cDNA-AFLP and RNA-Seq transcriptomic analysis: cytochromes P450, ABC transporters, glycosyitransferases, UDPglucuronosyl/glucosyItransferases and glutathione S-transferases. This results combined with increased phytotoxicity of imazetapyr ¡n the resistant line when P450s inhibitors were present, agree with suggestions previously made that non-target-site resistance mechanisms may contribute to herbicide resistance ¡n sunflower. Moreover, these mechanisms could be related to the modifier locus lmr2. This study allowed to detect constitutively expressed detoxification genes potentially related to imidazolinone resistance in sunflower and encourage further experimentation on the molecular and biochemical levels to asses the role of P450s in endowing herbicide resistance.